Formation of professional independence in the process of obtaining a legal education - Zelenov, Ph. D. Yuri N.; Gubareva, Ph. D. Anna V.; Kovalenko, Ph. D. Kseniya E. (Revista Conrado, 2017)
Los requisitos modernos para mejorar la calidad de vida en Rusia están relacionados con la mejora continua de la actividad humana, mejorando su efectividad mediante la optimización y el aumento de la intensidad de la ciencia, buscando e implementando las tecnologías más efectivas. La solución de estos problemas es prácticamente imposible sin la independencia profesional. La independencia profesional, en nuestra opinión, es una cualidad compleja, cuya estructura incluye las características morales, intelectuales y de actividad de individuos o colectivos que actúan en ciertas esferas. La naturaleza creativa de la actividad legal está determinada por el dinamismo e individualidad de las situaciones en que se lleva a cabo, la exclusividad del comportamiento de sus participantes, la ausencia en la mayoría de los casos de instrucciones inequívocas sobre los métodos y medios para regular las relaciones legales, la imposibilidad de aplicar instrucciones obligatorias, la irrepetibilidad de las condiciones reales que surgen en la regulación legal. Palabras clave: Independencia profesional, educación legal, competencia, proceso educativo. ABSTRACT The modern requirements for improving the quality of life in Russia are linked with the continuous improvement of human activity, improving its effectiveness through optimization and increasing the science intensity, searching and implementing the most effective technologies. The solution of these problems is practically impossible without the professional independence. Professional independence, in our opinion, is a complex quality, the structure of which includes the moral, intellectual and activity characteristics of the individual or collective acting in certain spheres. The creative nature of legal activity is determined by the dynamism and individuality of the situations in which it is carried out, the exclusivity of the behavior of its participants, the absence in most cases of unambiguous instructions on the methods and means of regulating the legal relationships, the impossibility of applying mandatory instructions, the unrepeatability of the real conditions that arise in legal regulation. Keywords: Professional independence, legal education, competence, educational process.